Consider that the equation of a straight line passing through two points is given by,
![y-y_1=(y_2-y_1)/(x_2-x_1)(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/hkbzvop4iz62zgm93u190774353c4ig6id.png)
The points are given as,
![\begin{gathered} (x_1,y_1)=(-3,7) \\ (x_2,y_2)=(9,-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/aqqqnf02wqn898g30d7fo5tw7w6xw4zc4b.png)
So the equation of line passing through these points is given by,
![\begin{gathered} y-7=\frac{(-1)-7_{}}{9-(-3)}(x-(-3)) \\ y-7=(-1-7)/(9+3)(x+3) \\ y-7=(-8)/(12)(x+3) \\ y-7=(-2)/(3)(x+3) \\ 3y-21=-2x-6 \\ 2x+3y-21+6=0 \\ 2x+3y-15=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e6v3rn46pnw3zu7j67as12kl6lreqhz7xp.png)
Thus, the equation of the line passing through the given points is 2x + 3y - 15 = 0 .